In Situ Fabricated Quasi‐Solid Polymer Electrolyte for High‐Energy‐Density Lithium Metal Battery Capable of Subzero Operation. Issue 2 (1st December 2021) - Yu, Jing; Lin, Xidong; Liu, Jiapeng; Yu, Jacky T. T.; Robson, Matthew J.; Zhou, Guodong; Law, Ho M.; Wang, Haoran; Tang, Ben Zhong; Ciucci, Francesco
Abstract: Solid‐state batteries (SSBs) are an emerging technology for safe and high‐energy‐density electrochemical energy storage. Unfortunately, SSBs suffer from inadequate ionic conductivity and sluggish interfacial transport at subzero temperatures, which limit their widespread application. Herein, a flexible, stable, and highly conductive quasi‐solid polymer electrolyte (QSPE) for SSBs is developed that allows low‐temperature (LT) operation. The in situ polymerized QSPE has an integrated battery structure, outstanding ionic conductivity (e.g., 1.0 mS cm −1 at −30 °C), and exhibits favorable compatibility with Li metal (>2000 h in Li|QSPE|Li). Li|QSPE|LiFePO4 and high‐voltage Li|QSPE|LiNi0.8 Mn0.1 Co0.1 O2 batteries demonstrate excellent long‐term stability (>2000 cycles at room temperature) and can operate effectively at LT (e.g., −30 °C). Furthermore, pouch cells with a LiNi0.8 Mn0.1 Co0.1 O2 (14.5 mg cm −2 ) cathode show flexibility, safety, and high capacity. The high performance of this QSPE is ascribed to its unique multilayer solvation structure that provides fast Li + transport and excellent interfacial stability. Thus, the newly developed electrolyte chemistry enables practical high‐voltage, LT solid‐state Li batteries. Abstract : This work reports the development of a flexible, stable, and highly conductive quasi‐solid polymer electrolyte (QSPE) for solid‐state Li metal batteries. The corresponding Li|QSPE|LiFePO4 and high‐voltage Li|QSPE|LiNi0.8 Mn0.1 Co0.1 O2 batteries demonstrate excellent long‐term stability (>2000 cycles at room temperature) and can operate effectively at low temperature (e.g., −30 °C), respectively.